Rezultati postopkov oploditve z biomedicinsko pomočjo v mariborskem centru v primerjavi s povprečnimi rezultati v slovenskih in evropskih centrih (Evropski IVF monitoring 2000-2005) - Reljič, Milan (Zdravniški vestnik, 2011)
Background: The aim of the European IVF Monitoring is to compare the accessibility, and the success of the implementation of assisted reproductive technology (ART) among European countries. In this article we compared the success of Maribor IVF centre with Slovenian and European success rates. Materials and methods: Pooled data for Europe, Slovenia and Maribor from the last six EIM reports are shown in tables. Results: During 2000- 2005, the number of ART cycles, the percentage of intracytoplasmic sperm injection (ICSI) and frozen embryo replacement (FER) in Europe increased. In that period the same trend was observed in Slovenia. The percentage of children born after ART in Europe was between 0.2 %-4.2 %. In Slovenia this percentage was among the highest among the European countries, and was 3.9 % in 2005. The age structure of female patients in Slovenia did not differ from that in other European countries, but the percentage of women older than forty years increased. In European countries the transfer of two or three embryos was the most frequent, however the percentage of single embryo transfers increased, which was most notable in Maribor IVF centre. Pregnancy rates were comparable among European countries and our centers, while pregnancy rate in IVF and ICSI in Maribor IVF centre was slightly higher. In 2005, the percentage of twin pregnancies in Maribor IVF centre decreased and was 24 %, however it was slightly higher than European and Slovenian averages. The ovarian hyperstimulation syndrome (OHSS) was the most common complication of ART, which appeared in less than 1 %. Conclusion: In Maribor and other Slovenian IVF centers accessibility and success of ART in the observed period were above the European average.
Keywords: Europe; Evropa; fertilization; oploditev; oploditev z biomedicinsko pomočjo; uspešnost